If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 = -34m + -55 Reorder the terms: 47 = -55 + -34m Solving 47 = -55 + -34m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '34m' to each side of the equation. 47 + 34m = -55 + -34m + 34m Combine like terms: -34m + 34m = 0 47 + 34m = -55 + 0 47 + 34m = -55 Add '-47' to each side of the equation. 47 + -47 + 34m = -55 + -47 Combine like terms: 47 + -47 = 0 0 + 34m = -55 + -47 34m = -55 + -47 Combine like terms: -55 + -47 = -102 34m = -102 Divide each side by '34'. m = -3 Simplifying m = -3
| y=3(-2)-8 | | 4(x-9)=32 | | g-42=13 | | 45+13x=180 | | -7(4y-3)+6y=-177 | | N+2(N+1)=8 | | 4y-9=16x | | 180-(8x+3)=15x-7 | | 2+4r=5(r-1) | | 5x^3-5x^2-2x=0 | | -6a-15=-5t+3-2t | | 15x-13=7x+11 | | 3(A-4)=3 | | 10x+15=5x-30 | | 23=k+12 | | 6+2(2x-3)=36 | | 13x-17=4x+10 | | 23/38+54x=.75 | | 9x-7=8x+8 | | 3x-2+x+10+x=48 | | 5(3y-2)+5y=-10 | | 12x-7=5x+7 | | 12n=3n+27 | | a/3=0 | | 6x+12=4x+24 | | 20x-7=16x+9 | | 3xn=27 | | 39=-5x+19 | | 14p-2(3p-7)=3(3p-7)-8p | | 6y=4x-20 | | 9=-5x+19 | | 19=-5x+19 |